Student Perceptions of the Effectiveness of the Makassar State University Bidikmisi Tuition Fee Assistance Program - Jamaluddin Jamaluddin; Andi Intan Aulia; Muh. Nasrullah; Muhammad Darwis; Risma Niswaty (Jurnal Ad'ministrare, 2022)
An illustration of the extent to which program effectiveness is needed for evaluation purposes. This study aims to determine the student's perception of the effectiveness of the Bidikmisi Education Fee Assistance Program, Makassar State University. In order to realize this, a qualitative descriptive research type was used with research subjects as many as nine program beneficiaries from nine different faculties. Research data collection uses three alternatives (observation, interviews and documentation). The data obtained from the research results were processed using data analysis techniques, namely (data collection, data condensation, data presentation and verification/drawing conclusions). The results showed that based on student perceptions, the effectiveness of the Bidikmisi tuition assistance program, Makassar State University was not yet in the effective category, seeing several indicators that became benchmarks (accuracy of program targets, program socialization, program objectives and monitoring of the program) overall less effective aspects still require attention and optimal supervision of parties related to program implementation. Regarding the superiority of research in representing the power of literacy, especially through scientific writing, research shows that literacy is able to accommodate the aspirations of not only one, but even many heads.